(untitled) (Scientific journal of the Fergana State University, 2023)
The given article is devoted to analysis of the chain associative raw, defining the individuality and peculiar characteristics of the associative links, which can accumulate during the whole life of the person, revealing the semantic relations between the words and including the words into semantic word families.